Re-layout Laboratorium Pengujian Lingkungan Dengan Menggunakan Metode SLP (Systematic Layout Planning) pada PT ABC - Ihsan, Tiaradia; Guna, Sura (Peneliti.net, 2024)
PT.ABC is a company operating in the environmental services sector. Planning the layout of laboratory facilities is an important issue, because the company will operate for a long period of time. Based on observations, the problem with the layout at PT. ABC is that there are several rooms that are too far apart, which results in the sample analysis process being less effective and efficient. Therefore, it is very necessary to redesign the layout of laboratory facilities to reduce the distance between stations in the analysis process in order to optimize production process time. The method used for layout design is Systematic Layout Planning (SLP).